Epidemiology of urticaria in infants and young children in Germany – Results from the German LISAplus and GINIplus Birth Cohort Studies. Issue 1 (17th November 2013) - Brüske, I.; Standl, M.; Weidinger, S.; Klümper, C.; Hoffmann, B.; Schaaf, B.; Herbarth, O.; Lehmann, I.; von, A.; Berdel, D.; Bauer, C. P.; Koletzko, S.; et al.
Abstract Background Although urticaria is considered one of the most frequent skin diseases, reliable epidemiologic data are scarce. Objective To evaluate the incidence and cumulative prevalence of urticaria in infants and children up to age of 10, to characterize the relationship of specific IgE levels (food and inhalative allergens) with urticaria, and to monitor the joint occurrence of urticaria with other diseases, such as eczema, asthma, and hay fever. Methods The study population consisted of two prospective birth cohort studies: the LISAplus and GINIplus studies. Information on physician‐diagnosed urticaria, asthma, eczema, or hay fever was collected using self‐administered questionnaires completed by the parents. Blood samples were drawn, and specific immunoglobulin E measured at 2 (only LISAplus), 6 and 10 yr of age. Results The incidence of urticaria was approximately 1% per year of age. The cumulative prevalence of urticaria in children up to the age of 10 yr was 14.5% for boys and 16.2% for girls. Cumulative prevalence of urticaria at the age of ten was significantly (p < 0.05) associated with allergic sensitization to peanut, soy, and wheat flour, but not with inhalant allergens. Both a parental history of atopy/urticaria and the children's diagnosis of asthma, eczema, and hay fever were strongly related (p < 0.0001) to the occurrence of urticaria. Conclusions Urticaria is a frequent event during childhood, with highest incidence in infants and preschool children. Comorbidity with atopic disease is high.